High-purity quartz sand purification process
Through the high-temperature semi-melt-re-sand composite process, the problem of difficult removal of mineral inclusion impurities in quartz is solved, and a quartz sand purification process with high purity and particle size control is realized, meeting the requirements of high-end applications.
Patent Information
- Application Number
- CN202411513237.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-28
- Publication Date
- 2025-02-18
AI Technical Summary
The prior art is difficult to effectively remove the mineral inclusion impurities present in quartz, resulting in the purity and performance of quartz products not reaching high standards.
The high-temperature semi-melt-re-sand composite process is adopted, including crushing, grinding, primary purification, semi-melt processing and oxidation and roasting, and the impurities of mineral inclusions in quartz are removed and the particle size of quartz sand is controlled.
It realizes effective removal of mineral inclusion impurities in quartz, improves the purity and particle size control ability of quartz sand, and meets the requirements of high purity and particle size of quartz sand in different fields.
Smart Images

Figure CN119461830A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of high-purity quartz preparation, and in particular relates to a high-purity quartz sand purification process. Background Art
[0002] Ultra-high purity quartz (SiO2 purity ≥ 99.998%) is a key material in high-tech industries. It is not only used in the photovoltaic industry of new energy, but is also an indispensable material in the semiconductor field.
[0003] Impurities in high-purity quartz ore are key factors affecting its purity and performance. Gangue mineral impurities are minerals that appear in the same space as quartz, also known as co-existing independent gangue minerals, such as feldspar, mica, rutile, calcite, fluorite, hematite, pyrite and clay minerals, etc. They are the main carrier minerals of impurity elements in quartz, and they are easy to become mineral inclusions in quartz during the geological mineralization process, which is an important factor restricting the purity and performance of quartz products. Obviously, the easiest way to remove this kind of mineral inclusion impurities growing inside quartz is to grind the quartz particles to the same particle size as the mineral inclusion impurities to completely dissociate the two.
[0004] However, there are strict requirements for quartz particle size in different application fields. For example, in the fields of ultra-high purity quartz such as photovoltaics and semiconductor industries, quartz sand is usually required to be in the range of 0.075~0.25mm, while the average particle size of mineral inclusion impurities is finer than that. This makes it difficult to remove such inclusion impurities through traditional physical beneficiation methods such as grinding, and can only be purified by chemical beneficiation methods such as calcination water quenching, hot pressing acid leaching, etc. However, such beneficiation methods are usually costly and cannot guarantee the targeted and clean removal of mineral inclusion impurities in quartz, resulting in the inability to improve the purity of silica. Summary of the invention
[0005] In view of the above deficiencies in the prior art, the object of the present invention is to provide a high-purity quartz sand purification process to solve the problem that quartz and gangue minerals are difficult to dissociate.
[0006] To achieve the above object, the present invention is implemented through the following technical solutions: A high-purity quartz sand purification process comprises the following steps: S1. The quartz ore is crushed and ground in sequence to obtain a first quartz material; S2. The first quartz material is preliminarily purified to obtain a second quartz material; S3. Under a vacuum environment, the second quartz material is heated to a semi-molten state, and after cooling, a third quartz material is obtained; S4. The third quartz material is subjected to sand making to obtain high-purity quartz sand.
[0007] Preferably, in step S1, the particle size of the first quartz material is ≤-0.045 mm.
[0008] Preferably, in step S2, the primary purification process includes: sequentially performing gravity separation, magnetic separation, flotation, calcination and water quenching, hot pressing and acid leaching, and chlorination roasting on the first quartz material.
[0009] Preferably, in step S3, the heating temperature is 1400-1600° C., and the heating time is 60-90 min.
[0010] Preferably, in step S3, the second quartz material is heated in a high-purity graphite crucible.
[0011] Preferably, in step S4, before the third quartz material is subjected to sand making, the third quartz material is also subjected to oxidative roasting treatment.
[0012] Preferably, the third quartz material is subjected to oxidation roasting treatment in a high-purity quartz crucible.
[0013] Preferably, the temperature of the oxidative roasting is 950-1000° C., and the roasting time is 30-60 min.
[0014] Preferably, in step S4, the sand making method is: mixing the third quartz material with the iron medium and grinding to obtain a quartz sand sample, and then hot pressing and acid leaching the quartz sand sample to obtain high-purity quartz sand.
[0015] The present invention also provides a quartz glass, which is prepared using the high-purity quartz sand prepared by the above-mentioned high-purity quartz sand purification process as a raw material.
[0016] The beneficial effects of the present invention are: The present invention firstly crushes, grinds and preliminarily purifies the quartz ore, and then uses a high-temperature semi-melting-re-sand making composite process to not only effectively remove impurities in mineral inclusions in quartz and obtain quartz sand concentrate with higher grade and lower impurity element content, but also can control the quartz sand particle size to within the product requirement range, while meeting the requirements of different fields for quartz sand purity and particle size. BRIEF DESCRIPTION OF THE DRAWINGS
[0017] In order to more clearly illustrate the technical solution of the embodiment of the present invention, the drawings of the embodiment are briefly introduced below.
[0018] Figure 1 A process flow chart of high-purity quartz sand purification provided by an embodiment of the present invention; Figure 2 This is a picture of a glass body prepared using the high-purity quartz concentrate obtained in Example 1 of the present invention and Comparative Example 1 as raw materials; Figure 3This is a picture of a glass body prepared using the high-purity quartz concentrate obtained in Example 2 of the present invention and Comparative Example 2 as raw materials; Figure 4 This is a picture of glass prepared using the high-purity quartz concentrate obtained in Example 3 of the present invention and Comparative Example 3 as raw materials. DETAILED DESCRIPTION
[0019] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0020] In various industrial applications of high-purity quartz, especially high-end applications such as semiconductors, inclusion impurities are the most harmful impurities and one of the main factors affecting the purity of quartz products. Mineral inclusions are commonly found in quartz minerals. Their types and abundance depend on the crystallization environment and the alteration and deformation after crystallization, and can be observed through an optical microscope. In theory, all minerals that appear in the ore-forming parent rock can appear in quartz as mineral inclusions. Different parent rocks will produce different mineral inclusions in quartz. The main inclusions are feldspar, mica, and rutile.
[0021] Since the average particle size of mineral inclusion impurities is generally finer than the particle size range of high-purity quartz sand products for industrial applications, it is difficult to remove them from quartz by conventional physical purification methods such as gravity separation, magnetic separation, and flotation. Chemical methods such as calcination and water quenching, hot pressing and acid leaching, and chlorination roasting are usually considered for removal. The principle of chemical methods for removing mineral inclusions in quartz is to open the channels leading to the interior of the quartz through high temperature difference and high pressure, so that the mineral inclusions are exposed to the air, and then remove the mineral inclusions inside the quartz through physical or chemical means such as flotation and hot pressing and acid leaching. The disadvantages of this method are low efficiency and high cost, because the channels leading to the interior of the quartz are not targeted, which means that the opened channels do not necessarily lead to mineral inclusions, and frequent high temperature difference and high pressure will greatly change the surface properties and morphology of quartz, thereby reducing the quality of quartz sand, which may result in degradation in its industrial application.
[0022] In order to solve the above problems, the present invention provides a high-purity quartz sand purification process. Figure 1 As shown, the following steps are included: (1) Raw material crushing and grinding: The quartz ore is crushed and ground in sequence to obtain the first quartz material.
[0023] The present invention grinds the crushed quartz ore until the particle size range is ≤-0.045mm. Grinding is the primary process of quartz sand purification and processing, which has an important impact on subsequent processes. During grinding, firstly, the fine target particle size will enable the efficient removal of film impurities on the quartz surface, which will significantly improve the removal effect of the subsequent purification process; secondly, the quartz particles can be opened along the gaps between the grains, and the gangue minerals and mineral inclusions between the gaps will be dissociated into monomers or exposed on the quartz surface, which significantly improves the removal effect of the subsequent physical and chemical purification processes.
[0024] (2) Preliminary purification: The first quartz material is subjected to preliminary purification to obtain a second quartz material.
[0025] The primary purification process of the present invention can be any physical or chemical purification method known in the art, for example, physical and chemical methods such as gravity separation, magnetic separation, flotation, calcination and water quenching, hot pressing acid leaching and chlorination roasting are used to remove iron-containing minerals and intergrowth particles and associated gangue minerals such as feldspar and mica in the silica mineral raw materials. The primary purification greatly reduces the mineral inclusion impurities in the first quartz material, realizes the controllability of trace elements, and avoids the influence of mineral inclusion impurities on the chemical stability, expansion coefficient and thermal conductivity of the subsequent semi-molten quartz processing.
[0026] (3) Semi-molten processing: Under a vacuum environment, the second quartz material is heated to a semi-molten state, and after cooling, the third quartz material is obtained.
[0027] Specifically, the second quartz material is placed in a high-purity graphite crucible, heated to 1400-1600°C in a vacuum environment, and kept warm for 60-90 minutes. During this process, the graphite crucible is well preserved due to the vacuum environment, and the granular second quartz material transitions from solid to liquid and forms a semi-molten state in which the solid phase and the liquid phase coexist. After cooling, the third quartz material in a solid block is obtained. Since this process is vacuum throughout, it also prevents "artificial gas inclusions" from mixing into the third quartz material.
[0028] Specifically, "artificial gas inclusions" are formed when air is mixed into the quartz material during the transition from solid to liquid, and cannot be removed in time after cooling.
[0029] The method of solid-state forming by semi-molten quartz heating of the present invention is a processing method that makes full use of the semi-solid characteristics of quartz when it transitions from solid to liquid (solid and liquid coexist). Quartz sand is placed in a high-purity graphite crucible and heated to 1400-1600°C where the internal solid phase and liquid phase are in a stable coexistence state. After aging treatment, a solid-state formed quartz product is obtained, which enables the above-mentioned fine-grained quartz sand particles to complete the transformation from granular to blocky and still retain their natural quartz characteristics. At the same time, the above method uses a high-purity graphite crucible, so that the interface thermal stress between the semi-molten quartz product and the graphite crucible is much smaller than the interface thermal stress between the simple quartz product and the quartz crucible, thereby greatly improving the plasticity and formability of the semi-molten quartz product.
[0030] (4) Oxidation roasting: Place the third quartz material in a high-purity quartz crucible and perform oxidation roasting in an oxygen environment. The roasting temperature is 950-1000°C and the roasting time is 30-60 min.
[0031] The oxidation roasting method adopted by the present invention is based on a removal and oxidation reaction of a small portion of graphite remaining and physically adhering to the surface of the quartz product after the above-mentioned semi-melting process. Therefore, after the above-mentioned semi-melting process is completed, the naturally cooled quartz product is taken out and placed in a high-purity quartz crucible for oxidation and impurity removal reaction to remove the residual graphite in the third quartz material: C+O2=CO2.
[0032] (5) Sand making: The quartz material after oxidation roasting is subjected to sand making to obtain high-purity quartz sand products with target particle size.
[0033] The sand making process of the present invention can be any sand making method known in the art, as long as the block quartz can be converted into quartz sand of the target particle size. For example, the block quartz material obtained after oxidation roasting is mixed with an iron medium for grinding to obtain a quartz sand sample, and then the quartz sand sample is hot-pressed and acid-leached to remove the iron-stained medium on the surface, and finally high-purity quartz sand is obtained.
[0034] In order to make the purpose, technical scheme and advantages of the present invention clearer, the embodiments of the present invention will be further described in detail below. Unless otherwise specified, the process conditions of the following examples are conventional methods known in the art, such as conventional physical and chemical processes such as dry magnetic separation, flotation, calcination and water quenching, hot pressing acid leaching and chlorination roasting, and conventional hot pressing acid leaching processes known in the art.
[0035] Example 1 1) The quartz ore of a certain vein is first classified and washed to remove the clay on the surface of the mineral, and then crushed in the first stage and the second stage to obtain coarse-grained quartz particles in the particle size range of 4~25mm. The above coarse-grained quartz particles are ground to a particle size range of -0.045mm by a first-stage iron medium grinding process to obtain the first quartz material. The first quartz material is subjected to conventional physical and chemical high-purity quartz purification processes such as dry magnetic separation, flotation, calcination and water quenching, hot pressing acid leaching and chlorination roasting to obtain high-purity quartz primary powder, i.e., the second quartz material.
[0036] 2) The high-purity quartz primary powder is placed in a high-purity graphite charging crucible, and heated in a heating furnace under a vacuum environment to 1400°C when the solid phase and liquid phase inside the quartz are in a stable coexistence state, and then kept warm for 90 minutes. After the protective gas is introduced to completely discharge the toxic gases such as CO in the furnace, it is naturally cooled to obtain a solid-state formed quartz block, i.e., the third quartz material.
[0037] 3) After naturally cooling, the quartz block is taken out and placed in a high-purity quartz crucible, and heated to 950°C in a heating furnace under air atmosphere and kept warm for 60 minutes. After the roasting operation is completed and the temperature in the furnace drops to room temperature, the quartz crucible is taken out to obtain a high-purity solid quartz block.
[0038] 4) The high-purity solid quartz block is placed in a grinding machine for iron medium wet grinding to obtain a quartz sand sample with a target particle size range of 0.106~0.25mm; a predetermined amount of the above quartz sand sample is taken for shock hot pressing acid leaching, and the acid used is hydrofluoric acid. After the acid leaching operation is completed, a high-purity quartz concentrate with a final purity of 4N9 grade is obtained.
[0039] Comparative Example 1 The same vein quartz ore as in Example 1 is crushed, ground, and physically and chemically treated to obtain high-purity quartz powder, specifically: the vein quartz ore of a certain place is first classified and washed to remove clay on the surface of the mineral, and then crushed in the first stage and the second stage to obtain coarse-grained quartz particles in the particle size range of 4 to 25 mm. The above coarse-grained quartz particles are ground to a particle size range of -0.045 mm by a first-stage iron medium grinding process to obtain a first quartz material. The first quartz material is subjected to conventional physical and chemical high-purity quartz purification processes such as dry magnetic separation, flotation, calcination and water quenching, hot pressing acid leaching and chlorination roasting to obtain high-purity quartz powder.
[0040] The chemical elements in the quartz sand obtained in Example 1 and Comparative Example 1 are shown in Table 1.
[0041] Table 1
[0042] As can be seen from Table 1, the quartz sand obtained in Example 1 is a high-purity quartz concentrate with a purity of 4N9 grade. Compared with the conventional quartz purification process in Comparative Example 1, the contents of impurity Ti elements and main alkali metal impurities Li, Na, and K elements in the concentrate obtained in Example 1 are lower than those in the concentrate sample of Comparative Example 1, indicating that the process of the present invention can obtain quartz concentrate with higher purity.
[0043] The high-purity quartz concentrate obtained in Example 1 and Comparative Example 1 were used as raw materials to prepare glass bodies by hydrogen-oxygen flame firing. Figure 2 As shown, it can be seen that the bubbles in the glass obtained by the quartz sand obtained after purification by the process of Example 1 are significantly less than those in Comparative Example 1, indicating that the quartz sand prepared by the high-purity quartz sand purification process provided by the present invention can be used to prepare high-end downstream products such as glass and semiconductors.
[0044] Example 2 1) The raw ore of pegmatite quartz A from a certain place is first classified and washed to remove clay on the surface of the mineral, and then crushed in the first stage and the second stage to obtain coarse-grained quartz and mixed particles of middle-veined minerals in the particle size range of 4~25mm. The above coarse-grained particles are ground to a particle size range of -0.075mm by a first-stage iron medium grinding process to obtain the first quartz material. The first quartz material is subjected to conventional physical and chemical high-purity quartz purification processes such as dry magnetic separation, flotation, calcination and water quenching, hot pressing acid leaching and chlorination roasting to obtain high-purity quartz primary powder, i.e., the second quartz material.
[0045] 2) The high-purity quartz primary powder is placed in a high-purity graphite charging crucible, and heated in a heating furnace under a vacuum environment to 1500°C when the solid phase and liquid phase inside the quartz are in a stable coexistence state, and then kept warm for 60 minutes. After the protective gas is introduced to completely discharge the toxic gases such as CO in the furnace, it is naturally cooled to obtain a solid-state formed quartz block, i.e., the third quartz material.
[0046] 3) After naturally cooling, the quartz block is taken out and placed in a high-purity quartz crucible, and heated to 950°C in a heating furnace under air atmosphere and kept warm for 30 minutes. After the roasting operation is completed and the temperature in the furnace drops to room temperature, the quartz crucible is taken out to obtain a high-purity solid quartz block.
[0047] 4) The high-purity solid quartz block is placed in a grinding machine for iron medium wet grinding to obtain a quartz sand sample with a target particle size range of 0.09-0.18 mm; a predetermined amount of the above quartz sand sample is taken for shock hot pressing acid leaching, and the acid used is hydrofluoric acid. After the acid leaching operation is completed, a high-purity quartz concentrate with a final purity of 4N8 grade is obtained.
[0048] Comparative Example 2 The difference from Example 2 is that only the crushing-grinding-physical and chemical treatment steps of step 1) are performed to obtain high-purity quartz powder.
[0049] The chemical elements in the quartz sand obtained in Example 2 and Comparative Example 2 are shown in Table 2.
[0050] Table 2
[0051] As can be seen from Table 2, compared with the conventional quartz purification process of Comparative Example 2, the contents of impurity Al, Ca elements and main alkali metal impurities Li, Na, and K elements in the concentrate obtained in Example 2 are lower than those in the concentrate sample of Comparative Example 2, indicating that the process of the present invention can obtain quartz concentrate with higher purity. And from the abnormally high impurity Al, Li, Na, and K elements in the chemical element table of Comparative Example 2, it can be inferred that the quartz sand of Comparative Example 2 contains mineral inclusions, from which it can be seen that the process of the present invention can remove mineral inclusions in quartz particles.
[0052] The high-purity quartz concentrate obtained in Example 2 and Comparative Example 2 were used as raw materials to prepare glass bodies by hydrogen-oxygen flame firing. Figure 3 As shown, it can be seen that the bubbles in the glass obtained by quartz sand obtained after purification by the process of Example 2 are significantly less than those in Comparative Example 2, and it can be seen that the glass product of Comparative Example 2 has a large number of bubbles, which is consistent with the speculation that the mineral inclusions are contained in the above Comparative Example 2. This shows that the high-purity quartz sand purification process provided by the present invention can remove mineral inclusions in quartz particles, and the quartz sand prepared by the process can be used to prepare high-end downstream products such as glass and semiconductors.
[0053] Example 3 1) The raw ore of pegmatite quartz B in a certain place is first classified and washed to remove clay on the surface of the mineral, and then crushed in the first stage and the second stage to obtain coarse-grained quartz and mixed particles of middle-veined minerals in the particle size range of 4~25mm. The above coarse-grained particles are ground to a particle size range of -0.075mm by a first-stage iron medium grinding process to obtain the first quartz material. The first quartz material is subjected to conventional physical and chemical high-purity quartz purification processes such as dry magnetic separation, flotation, calcination and water quenching, hot pressing acid leaching and chlorination roasting to obtain high-purity quartz primary powder, i.e., the second quartz material.
[0054] 2) The high-purity quartz primary powder is placed in a high-purity graphite crucible, and heated in a heating furnace under a vacuum environment to 1600°C when the solid phase and liquid phase inside the quartz are in a stable coexistence state. The temperature is kept for 70 minutes, and after the protective gas is introduced to completely discharge the toxic gases such as CO in the furnace, the solid-state formed quartz block is obtained by natural cooling, i.e., the third quartz material.
[0055] 3) After naturally cooling, the quartz block is taken out and placed in a high-purity quartz crucible, and heated to 1000°C in a heating furnace under air atmosphere, and kept warm for 45 minutes. After the roasting operation is completed and the temperature in the furnace drops to room temperature, the quartz crucible is taken out to obtain a high-purity solid quartz block.
[0056] 4) The high-purity solid quartz block is placed in a grinding machine for iron medium wet grinding to obtain a quartz sand sample with a target particle size range of 0.09-0.25 mm; a predetermined amount of the above quartz sand sample is taken for shock hot pressing acid leaching, and the acid used is hydrofluoric acid. After the acid leaching operation is completed, a high-purity quartz concentrate with a final purity of 4N8 grade is obtained.
[0057] Comparative Example 3 The difference from Example 3 is that only the crushing-grinding-physical and chemical treatment steps of step 1) are performed to obtain high-purity quartz powder.
[0058] The chemical elements in the quartz sand obtained in Example 3 and Comparative Example 3 are shown in Table 3.
[0059] Table 3
[0060] As can be seen from Table 3, compared with the conventional quartz purification process of Comparative Example 3, the contents of main alkali metal impurities Li, Na and K in the concentrate obtained in Example 3 are much lower than those in the concentrate sample of Comparative Example 3, indicating that the process of the present invention can obtain quartz concentrate with higher purity.
[0061] The quartz concentrate obtained in Example 3 and Comparative Example 3 was used as raw material to prepare a glass body by hydrogen-oxygen flame firing method. Figure 4 As shown, it can be seen that the bubbles in the glass obtained by the quartz sand obtained after purification by the process of Example 3 are significantly less than those in Comparative Example 3, indicating that the quartz sand prepared by the high-purity quartz sand purification process provided by the present invention can be used to prepare high-end downstream products such as glass and semiconductors.
[0062] The percentage of completely transparent particles in the quartz concentrate obtained in Examples 1 to 3 and Comparative Examples 1 to 3 is shown in Table 4.
[0063] Table 4 Comparison of quartz concentrate indicators
[0064] It can be seen from Table 4 that compared with the conventional purification process of the comparative example, the quartz concentrate obtained by the high-purity quartz sand purification process provided by the present invention has a lower content of gas-liquid inclusions and more transparent particles, which is conducive to the subsequent preparation of high-end downstream products such as glass, photovoltaics, and semiconductors.
[0065] The above-mentioned embodiments only express the implementation methods of the present invention, and the descriptions thereof are relatively specific and detailed, but they cannot be understood as limiting the scope of the invention patent. It should be pointed out that, for ordinary technicians in this field, several variations and improvements can be made without departing from the concept of the present invention, which all belong to the protection scope of the present invention. Therefore, the protection scope of the patent of the present invention shall be subject to the attached claims.
Claims
1. A high-purity quartz sand purification process, characterized in that: The following steps are involved: S1. The quartz ore is crushed and ground in sequence to obtain a first quartz material; S2. The first quartz material is preliminarily purified to obtain a second quartz material; S3. Under a vacuum environment, the second quartz material is heated to a semi-molten state, and after cooling, a third quartz material is obtained; S4. Making sand from the third quartz material to obtain high-purity quartz sand.
2. The high-purity quartz sand purification process according to claim 1, characterized in that: In step S1, the particle size of the first quartz material is ≤-0.045 mm.
3. The high-purity quartz sand purification process according to claim 1, characterized in that: In step S2, the primary purification process includes: sequentially performing gravity separation, magnetic separation, flotation, calcination and water quenching, hot pressing and acid leaching, and chlorination roasting on the first quartz material.
4. The high-purity quartz sand purification process according to claim 1, characterized in that: In step S3, the heating temperature is 1400-1600° C., and the heating time is 60-90 min.
5. The high-purity quartz sand purification process according to claim 1, characterized in that: In step S3, the second quartz material is heated in a high-purity graphite crucible.
6. The high-purity quartz sand purification process according to claim 5, characterized in that: In step S4, before the third quartz material is subjected to sand making, the third quartz material is subjected to oxidative roasting treatment.
7. The high-purity quartz sand purification process according to claim 6, characterized in that: The third quartz material is subjected to the oxidation roasting treatment in a high-purity quartz crucible.
8. The high-purity quartz sand purification process according to claim 6, characterized in that: The temperature of the oxidation roasting is 950-1000° C., and the roasting time is 30-60 min.
9. The high-purity quartz sand purification process according to claim 1, characterized in that: In step S4, the sand making method is: mixing the third quartz material with an iron medium to perform grinding to obtain a quartz sand sample, and then hot pressing and acid leaching the quartz sand sample to obtain the high-purity quartz sand.
10. A quartz glass, characterized in that: The method is prepared using high-purity quartz sand obtained by the high-purity quartz sand purification process described in any one of claims 1 to 9 as raw material.
Citation Information
Patent Citations
Crucible for electronic industry and method for purifying high-purity quartz sand as lining material
CN102120583A
Calcining method for high-purity silica sand
CN108751210A
Method for purifying quartz through directional solidification
CN111762789A
Method for purifying quartz by chloridizing roasting
CN111874913A
Method for preparing electronic-grade high-purity quartz sand
CN114378026A